(untitled) (Papeles, 2021)
This paper begins with Keynes’ text on the nature of economic thought where he states three stages of the cognitive process: i) ordered thought; ii) the disintegration of partial causalities, iii) the multi-causal perspective of phenomena. From there on, I explain that the value neutrality claim still gives the vain illusion of objective knowledge. Although there has been severe criticism of positivism in the history of economic thought, schools and economic professors still refuse to acknowledge the inevitable existence of prejudices. To deny that all knowledge is based on a priori notions absolutizes the method and stops thinking.